Analysis of Employee Spirituality on Organizational Behavior - Gifi Wansya Putri Haya (BANCO: Jurnal Manajemen dan Perbankan Syariah, 2021)
This article aims to study spirituality where it is a new discussion in the study of organizational behavior. By conducting a literature review, this article discusses the concept of spirituality, developments and research examples, as well as several theoretical concepts from previous research that can be used as a reference for the development and theoretical growth of spirituality studies on organizational behavior. In the future era, the study of spirituality can be further developed by strengthening the theoretical foundation and improving the design of empirical research methodologies.